Vytautas Kavolis: Liberalism and Metaphysics - Noreika, Alvydas (Sociologija. Mintis ir veiksmas, 2019)
The article deals with the Lithuanian-American political scholar Vytautas Kavolis’s approach to the metaphysical foundations of liberalism. It is argued that the scholar’s position in regard to this question has changed as time passed. Until the 1970s, Kavolis defended the position that pure (philosophical) liberalism does not presuppose any a priori metaphysics. It doesn’t dictate to its partisans in a normative way what they have to think about God, to accept His existence or not, or how they ought to treat reality as a whole. According to Kavolis, pure liberalism is neutral with regard to God and reality as a whole. It is an empty form in the metaphysical sense. The right to fill up an empty form with a metaphysical content is delegated to an individual in pure liberalism. From the 1970s, Kavolis took a much more moderate position regarding the metaphysical foundations of liberalism. In his view, pure liberalism is founded on some metaphysical presuppositions – namely, the metaphysical conception of order. Inquiring Kavolis’ approach to the metaphysical foundations of liberalism, wide attention is paid to its context of origin as well.